The impact of sales promotion by licensed buying companies on cocoa sales of farmers-a case study of Wassa Amenfi East District. - ADAMU, FUSEINI (KNUST, 2025)
A Thesis Submitted To The School Of Business-College Of Arts And Social Sciences, In Partial Fulfillment Of The Requirements For The Degree Of Masters Of Business Administration (MBA) (Marketing Option).